THE EFFECT OF PROFITABILITY, MANAGERIAL OWNERSHIP, AND FIRM SIZE ON TAX AVOIDANCE - Harvey Eddyson; Clara Susilawati (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the effect of profitability , managerial ownership, and firm size on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The research sample was obtained using purposive sampling . The number of samples in the study was 232. Data analysis used multiple linear regression. In this study , tax avoidance is not only seen as a tax saving strategy, but also as part of an effort to increase company efficiency in managing fiscal burdens legally. This efficiency allows companies to optimize operational cash flow, increase the availability of funds for investment, and strengthen long-term financial performance. These findings indicate that companies with high profitability, large company size, and strong managerial ownership tend to utilize tax planning strategies to achieve efficient use of resources and maximize company value. The results show that firm size , profitability , and managerial ownership have a positive and significant effect on tax avoidance .